ANALISIS METODE PENYUSUTAN AKTIVA TETAP TERHADAP LABA PERUSAHAAN - Benny Krisnanto, 03.05.52.0052; Badjuri, Achmad (Students Journal of Accounting and Banking, 2012)
Accounting treatment of fixed assets is an accounting treatment applied to fixed assets owned by the company. This treatment includes the cost of the asset, after the acquisition expenses, depreciation of fixed assets and the discharge or disposal of fixed assets. The purpose of this study was to look for possible accounting treatment of fixed assets are most appropriate to be applied to the fixed assets of the company. An analysis includes also the effect of calculating the depreciation of the companys income statement. For the writing of this script author conducted research on PT. Glora Karya Makmur located in Klepu Semarang. To obtain the data, performed data collection through library research and field research. Fieldwork was conducted by a brief interview with the competent authorities, as well as field observations to directly supervise the object under study. This study takes the object of fixed assets of Group II motor vehicle owned by PT. Glora Karya Makmur. Based on observations on PT. Glora Karya Makmur , it is known that the method of depreciation of fixed assets employed by the company is a straight-line depreciation method. From the analysis there were significant nominal effect of the depreciation method used by the company that is a straight-line method with sum of the year digit method and double declining balance method, so the company can generate greater profits.Keywords: Fixed Assets, Depreciation Method of Fixed Assets, Corporate Earnings, Literature Studies and Field Research.